1999
DOI: 10.1046/j.1365-3156.1999.43370.x
|View full text |Cite
|
Sign up to set email alerts
|

Bednet impregnation for Chagas disease control: a new perspective

Abstract: Summarybackground To determine the efficacy and acceptability of deltamethrin-impregnated bednets in controlling Chagas disease in South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 7 publications
0
34
0
3
Order By: Relevance
“…10 House improvement might be more appealing than other methods such as insecticide paints, which received low acceptance in communities in Honduras because of smells and secondary effects, 47 or bed nets, which were accepted by a population in Colombia but still require the introduction of foreign objects or practices. 48 House improvements should be complimented with peridomestic reservoir reduction because peridomestic triatominae foci can persist after house improvement. 24 A recent study in Guatemala showed good community acceptance of rodent control as part of an integrated vector management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…10 House improvement might be more appealing than other methods such as insecticide paints, which received low acceptance in communities in Honduras because of smells and secondary effects, 47 or bed nets, which were accepted by a population in Colombia but still require the introduction of foreign objects or practices. 48 House improvements should be complimented with peridomestic reservoir reduction because peridomestic triatominae foci can persist after house improvement. 24 A recent study in Guatemala showed good community acceptance of rodent control as part of an integrated vector management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of dispersal of sylvatic/peridomestic adult bugs into domestic areas with door/window screens or bed nets may prove to be a simple, cost-effective and sustainable complementary or alternative strategy to reduce house infestation by triatomines in this region (Kroeger et al 1999). The usefulness of such a strategy may not be limited to the Yucatán peninsula, as the transient infestation of houses by flying sylvatic adult bugs is thought to be responsible for a significant transmission of Chagas disease in several other regions (Coura et al 1994(Coura et al , 1999(Coura et al , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…An entomologic and epidemiologic system for surveillance of Chagas disease in Amazonia has been suggested (68,69). Alternatively, the enormous task of controlling emerging Chagas disease in the Amazon Basin should rely initially on an information, education, and communication program, which encourages control measures by the householder (e.g., use of screens, bed nets, insecticide-treated fabrics, and vegetation management) (69)(70)(71)(72)(73). Such a program for prevention of contact with triatomines should be conducted directly in communities, elementary schools, and churches and social clubs, reinforced by social marketing and mass media communications.…”
Section: Researchmentioning
confidence: 99%